Tekst pozwu sądowego w polskiej kodyfikacji prawa magdeburskiego z XVI wieku - Kość, Józef (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
In Porządek sądów i spraw miejskich prawa majdeburskiego w Koronie Polskiej published in Cracow in 1559 Bartłomiej Groicki had codified with respect to law regulations the text of a court summons. This codification also comprised the linguistic layer of the summons. The model of a summons text had been its oral and written text realizations in the court practice both in Polish and in Latin, which were previously known from mediaeval Polish, and also legal regulations included in professional legal literature written in Latin. Numerous reprints of Porządek sądów…, used through centuries in the court practice in Poland, contributed to the popularization and preservation of a summons in linguistic awareness of court officials and participants of court trials as a standard official utterance